Benzofenona difūzija no papīra un kartona iepakojuma uz pārtiku - Pugajeva, Iveta (Latvijas Universitāte, 2008)
Šajā darbā ir pētīta benzofenona difūzija no iepakojuma uz pārtiku. Tika izstrādāta un pārbaudīta metode benzofenona satura noteikšanai papīra un kartona iepakojumos ar AEŠH-MS-MS. Tika veikti pētījumi par benzofenona ekstrakcijas efektivitāti atkarībā no iepakojuma krāsas, laika, temperatūras un šķīdinātāja.

Information about migration of chemical compounds from packing to food has been summarized. More detailed information is given about paper and carton board packing and one of additive – benzophenone, which is used in manufacturing of this packing. Method of detection of benzophenone in paper and carton board packing on HPLC-MS-MS has been developed. Experiments for measurements of migration of benzophenone depending of time, temperature and solvent have been conducted.
Benzophenonae Diffusion from Paper and Cardboard containers to Food
Keywords: Ķīmija